Kombinasi Limbah Kulit Bawang Merah Dan Cangkang Telur Sebagai Pupuk Kompos Pada Tanaman Sayuran - Rukmana, Indah; Andi Irga Satrawati Taslim; Fatmawati Ramli (Jurnal Pengabdian Magister Pendidikan IPA, 2024)
This research aims to examine the use of a combination of onion skin waste and egg shells as compost for vegetable crops. This community service activity was carried out in Pekalobean Village, Anggeraja District, Enrekang Regency, involving the women farmer group (KWT) as the target. The methods used include outreach and training about making compost fertilizer, as well as its benefits and advantages compared to chemical fertilizers. The results of this activity show that the community is enthusiastic and able to understand and apply the knowledge gained in their agricultural practices. This training not only increases people's understanding of compost fertilizer, but also provides an environmentally friendly alternative to reduce dependence on chemical fertilizers. It is hoped that this activity can support sustainable agriculture and preserve the environment, as well as open up opportunities for further research regarding the effectiveness and innovation in making compost fertilizer from other natural materials.